DEKONSTRUKSI FENOMENA ISLAM SONTOLOYO DAN KRITIK FIKIH-SENTRISME: ANALISIS EPISTEMOLOGIS DAN SOSIO-TEOLOGIS TERHADAP FORMALISME BERAGAMA DI INDONESIA - Mu Minin, Dian Amirul; Ahmad Barizi; Basri Zain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to conduct a scientific deconstruction of the phenomenon of “Islam Sontoloyo,” as introduced by Ir. Soekarno, and to relate it to a critique of the tendency toward fiqh-centrism in Islamic thought in Indonesia. The phenomenon of Islam Sontoloyo is analyzed not as blasphemy, but rather as a form of self-criticism toward formalism and ritualism that have lost their spiritual substance and social transformative power. By employing the theoretical framework of Jacques Derrida’s deconstruction and Mohammed Arkoun’s critique of Islamic reason, this paper examines how logocentrism within the Islamic legal tradition has led to intellectual stagnation (jumud) and entrapment in binary oppositions that separate ritual piety from social justice. The findings indicate that fiqh-centrism tends to reduce the complexity of Islamic teachings into mere formalistic legalism, neglecting the broader objectives of the sharia (maqashid al-shari’ah). As a solution, this study explores the paradigm of Social Fiqh as developed by KH. Sahal Mahfudh, along with other reformist ideas in Islamic thought that emphasize a shift in legal adherence from a qawli (textual) approach to a manhaji (methodological) one. In conclusion, the study asserts that addressing the crisis of spirituality and religious alienation in the modern era requires a reconstruction of religious discourse that is more inclusive, dynamic, and accommodating of the cultural locality of the Indonesian archipelago, in order to restore the “spirit” of Islam as an instrument of liberation and humanity.